No difference in clinical outcomes in robotic-assisted vs. computer-navigated total hip arthroplasty - Haroun Haque; Ameer Tabbaa; Matthew Johnson; Lydia Fu; Afshin Razi; Matthew L. Magruder (Arthroplasty)
Abstract Background Robotic-assisted (RA) and computer-navigated (CN) total hip arthroplasty (THA) are increasingly performed, but prior studies comparing the two techniques and their outcomes were limited. This study aimed to compare clinical outcomes and costs of receiving THA using RA and CN technology. Methods We conducted a retrospective cohort study using a nationwide administrative database from January 1, 2010, to October 31, 2022. The study included patients undergoing THA either via RA (n = 4,473) or CN (n = 4,473) technology. Subjects were matched for age and pertinent comorbidities. Clinical outcomes evaluated included emergency department visits and readmissions within 90 days of surgery, lengths of stay, and implant-related complications within 90 days and 2 years of surgery. Costs were analyzed on the day of surgery and within a 90-day global period. Statistical analysis was performed using multivariate logistic regression analysis with a P < 0.01 considered statistically significant. Results There were no significant differences between the RA and CN cohort in ED visits or readmission within 90 days of surgery or in lengths of stay. Similarly, no differences were found in any of the implant-related complications at 90 days or 2 years following surgery. Same-day mean reimbursement for RA-THA was higher than for CN-THA ($4,472.23 vs. $3,890.61; P < 0.01). 90-day reimbursement did not differ significantly. Conclusion We demonstrated that readmission, ED visits, lengths of stay, and short-term implant-related outcomes did not differ between RA and CN-THA cohorts. Further studies are needed to explore the long-term benefits and cost implications of RA-THA.